Cryoanalgesia: Review with Respect to Peripheral Nerve - Slavin, Benjamin R.; Markowitz, Moses I.; Klifto, Kevin M.; Prologo, Frank J.; Taghioff, Susan M.; Dellon, A. Lee (Journal of Reconstructive Microsurgery, 2023)
Background Cryoanalgesia is a tool being used by interventional radiology to treat chronic pain. Within a certain cold temperature range, peripheral nerve function is interrupted and recovers, without neuroma formation. Cryoanalgesia has most often been applied to the intercostal nerve. Cryoanalgesia has applications to peripheral nerve surgery, yet is poorly understood by reconstructive microsurgeons.Methods Histopathology of nerve injury was reviewed to understand cold applied to peripheral nerve. Literature review was performed utilizing the PubMed and MEDLINE databases to identify comparative studies of the efficacy of intraoperative cryoanalgesia versus thoracic epidural anesthesia following thoracotomy. Data were analyzed using Fisher's exact and analysis of variance tests. A similar approach was used for pudendal cryoanalgesia.Results Application of inclusion and exclusion criteria resulted in 16 comparative clinical studies of intercostal nerve for this review. For thoracotomy, nine studies compared cryoanalgesia with pharmaceutical analgesia, with seven demonstrating significant reduction in postoperative opioid use or postoperative acute pain scores. In these nine studies, there was no association between the number of nerves treated and the reduction in acute postoperative pain. One study compared cryoanalgesia with local anesthetic and demonstrated a significant reduction in acute pain with cryoanalgesia. Three studies compared cryoanalgesia with epidural analgesia and demonstrated no significant difference in postoperative pain or postoperative opioid use. Interventional radiology targets pudendal nerves using computed tomography imaging with positive outcomes for the patient with pain of pudendal nerve origin.Conclusion Cryoanalgesia is a term used for the treatment of peripheral nerve problems that would benefit from a proverbial reset of peripheral nerve function. It does not ablate the nerve. Intraoperative cryoanalgesia to intercostal nerves is a safe and effective means of postoperative analgesia following thoracotomy. For pudendal nerve injury, where an intrapelvic surgical approach may be difficult, cryoanalgesia may provide sufficient clinical relief, thereby preserving pudendal nerve function.
Keywords: cryoanalgesia; peripheral nerve; peripheral nerve surgery